Pengaruh Persepsi Dukungan Organisasi dan Karakteristik Pekerjaan terhadap Employee Engagement pada Pegawai Negeri Sipil di Kabupaten X - Agus Iqbal Hawabi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Agencies or companies consider that an organization's success can be achieved only by having employees who have high competence. However, in reality, many highly competent employees cannot work optimally. This can be seen from the lack of employee enthusiasm for working (dedication) and low enthusiasm for completing work (vigor), so employee engagement with the organization is weak. This research aims to determine the influence of perceived organizational support and job characteristics on employee engagement. Data collection was carried out using the perceived organizational support scale created by Eisenberg (1986), the Hackman & Oldham (1976) job characteristics scale, and the Utrecht Work Engagement Scale created by Schaufeli et al. (2003). The results of this research show that perceptions of organizational support and job characteristics simultaneously influence employee engagement of Civil Servants in District X amounted to 61.6%, while changes in employee engagement were caused by other factors amounting to 38.4%.